EFFECT OF RACE, GENDER AND AGE ON THYROID AND THYROID STIMULATING HORMONE LEVELS IN NORTH WEST FRONTIER PROVINCE, PAKISTAN - Ahmed, Zahoor; Khan, Mudassir Ahmad; Haq, Amin ul; Attaullah, Salma; Rehman, Jamil ur (Journal of Ayub Medical College Abbottabad, 2009)
Background: Thyroid is one of the ductless endocrine gland, which is located immediately below the larynx on either side of and anterior to the trachea. The principal hormones of thyroid gland are thyroxine (T4) and triiodothyronine (T3). The current study was carried out to investigate the impact of race, gender and area on the levels of Thyroxine (T4), Triiodothyronine (T3) and Thyroid Stimulating Hormone (TSH) in normal healthy individuals. Methods: Serum levels of T4, T3 and TSH in 498 normal healthy individuals belonging to different districts of North West Frontier Province, Pakistan, were examined. Serum T4 and T3 were analysed by Radio Immuno Assay (RIA) method whereas TSH was estimated by Immunoradiometric assay (IRMA) method. Results: Levels of T4, T3 and TSH ranged from 53 to 167 Î·mol/L, 0.6 to 3.1 Î·mol/L and 0.3-4.8 µIU/L respectively. The levels of these hormones show significant change from the reference values that are used in clinical laboratories as well as in Institute of Radiotherapy and Nuclear Medicine (IRNUM), Peshawar, Pakistan. Conclusion: It is concluded that the age, gender, race and area, all have an appreciable effect on the levels T4, T3 and TSH. Keywords: Thyroxine, Triiodothyronine, Thyroid Stimulating Hormone, TSH, Thyroid Hormones